Multivariate Analysis of Hallux Valgus Radiographic Parameters - Meyr, Andrew J. (The Journal of foot and ankle surgery, 2022)
This investigation aimed to better understand the complex relationship of common radiographic measurements performed during the perioperative evaluation of the hallux valgus deformity while accounting for interactions and potential interdependence. Several analyses utilizing the first intermetatarsal angle, hallux valgus angle, tibial sesamoid position, Engel's angle, subject age and subject gender were performed with varying independent and dependent variables. The hallux valgus angle (p < .001), tibial sesamoid position (p < .001), and Engel's angle (p < .001) were found to be independently associated with the first intermetatarsal angle. The first intermetatarsal angle (p < .001), tibial sesamoid position (p < .001), and Engel's angle (p < .001) were found to be independently associated with the hallux valgus angle. This suggests that there is significant interdependence of these variables during a preoperative radiographic examination. However, only the change in tibial sesamoid position (p < .001) was found to be independently associated with the change in the first intermetatarsal angle following surgical correction, while no studied variables were found to be independently associated with the change in hallux valgus angle following surgical correction. This suggests that correction of the intermetatarsal angle and tibial sesamoid position might not always reliably predict correction of the hallux valgus angle following surgical intervention. It might also suggest that additional procedures beyond metatarsal osteotomies are required to reliably correct the hallux valgus angle in some deformities. It is hoped that this investigation adds to the body of knowledge with respect to the perioperative radiographic evaluation of the hallux valgus deformity.